The comparative morphology and the ontogeny of the genital system of the South African Arionids Ariopelta capensis and Ariostralis nebulosa with special reference to the phylogeny of the family Arionidae (Mollusca:Pulmonata) - Sirgel, W. F (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1984.